IMPLEMENTASI PERATURAN DAERAH KOTA DENPASAR NOMOR 27 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH KOTA DENPASAR DALAM HAL PEMANFAATAN RUANG TERBUKA HIJAU DI KOTA DENPASAR - Pramita Dewi, A. A. Sagung Istri; Sri Indrawati, A. A. (Kertha Negara : Journal Ilmu Hukum, 2013)
Population growth coupled with the need to show a very rapid increase. Theseconditions resulted in a need for information, one green open space information. Withthe information needed green space then issued Regulation No. 27 Denpasar 2011 onSpatial Planning in Denpasar that the regulations specified in Article 37 paragraph (1)letter e and in Article 42. The problem that arises is what is the basis for considerationof Denpasar Government sets green open space and how do we ensure people's right toland is designated as green open space. Tackling these problems Spatial Use reliedupon by the Denpasar Government in setting green open space and the Mayor issued aDecree No. Denpasar. 188.45/303/HK/2010 on the Granting Compensation PaymentLand and Building Tax Defined as the land is green open space. In discussing this issuejuridical empirical method is used, as it approaches the issue of legislation in force andthe reality that exists in society and the nature of the descriptive analytical study.
Keywords: Governance, Spatial, Open Green Space, Implementation